Synthetic Approaches to Lamivudine: An Anti-HIV AIDs and Anti-Hepititus B Drug - YAQUB, G.; HUSSAIN, E.A.; MATEEN, B. (Asian Journal of Chemistry, 2010)
Lamivudine is an extensively used drug in combinational therapies for treatment of AIDS and hepatitis B. Due to the presence of S, O acetal and stereogenic centres, the synthesis of lamivudine in good enantiomeric yield is a challenge for synthetic chemists. The main focus of this review article is to highlight systematically those few synthetic strategies which are reported in literature since its discovery in 1989 to approach this potent synthetic nucleoside analogue.